Analisis Perbedaan Likuiditas Saham dan Abnormal Return Sebelum dan Sesudah Right Issue Pada Perusahaan Go Publik DI Bursa Efek Indonesia (BEI) Tahun 2011-2012 - Pustaka, I Gede Abdi; Dewi S., Made Rusmala (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
The aim of this study was to determine the differences in stock liquidity and abnormal returns before and after the go public company's rights issue in Indonesia Stock Exchange (IDX) 2011-2012. This research was conducted at publicly traded company listed on the Indonesia Stock Exchange (IDX) during the years 2011-2012. This study used a sample of the entire population as 25 companies who conduct a rights issue during the year 2011-2012. Data was collected through non-participant observation method in which researchers collected data captured on topic. The data analysis technique used was paired sample t-test. Based on the analysis it was found that there was no significant difference in stock liquidity and abnormal returns before and after the rights issue. This shows that the information contained on the issuance of rights issue is not very attractive for investors. Investors assume that the announcement of the rights issue are not only the usual announcement greatly affect the performance of the company's shares and therefore investors are reluctant to invest in the company. Information leakage is likely to occur to make the rights issue announcement is assumed to not be an important information or announcements for investors.
Keywords: stock liquidity, abnormal return, right issue